کاریگەری پیداگۆژی داهێنەرانە لەسەر دەستکەوتی خوێندکاران - ل, پ. د. ئاراس فریق زه ینه; محمد, پ. ی. د. نزیره صالح; حیم, سیروان فائق محمود ره (Sulaimani Journal for Humanities, 2024)
The aim of the study 1- Knowledge effect of innovative pedagogy on the learning outcomes for the students. To prove the purpose of the study, the researcher developed a hypothesis that there was no statistically significant difference at level (0.05) between the students' score centers in the experiential group, which is taught by an innovative pedagogy strategy, and the scores of students in the control group who are taught in the same subject through the common test. The researchers relied on the experimental design of two balanced groups. The experimental group was taught subjects according to innovative pedagogy, and the control group was called the "belief-based" subjects. The research community consisted of students of the Elementary Education College and social sciences department of sulaymaniyah University in the border of Sulaymaniyah Governorate. For the academic year (2022-2023) The sample of this study consisted of students from the second stage of the social sciences department. It consisted of two groups: the researcher received (60) students as the sample of the Study (30) students from the experimental group of (30) students in the control group. In order to confirm the matching of the research groups in some of the related variables, the researcher conducted statistical matching by extracting the calculating center and deviation of the calculated Value (T) scales, such as student age, level of intelligence, and father's career. Last year's scores of students sampled the study. The researcher then developed a daily teaching plan to carry out the experience at the start of the second course of the (2022-2023) academic year and began implementing the program according to the prepared plan. For data collection, the researcher created an experiment for the content of the read subject, according to the classification levels of Benjamin Blum after completing the scientific requirements. The researcher then proceeded to share the data using (statistical center index deviation percentage Pearson correlation coefficient, independent (T.test). The researchers have found some of the results. The success of students in the experimental group resulted in a test that taught in an innovative pedagogy over the control group students who studied in a common manner. Research recommendations such as Providing training courses for university teachers to teach them new ways of teaching including innovative pedagogy.
Keywords: innovative pedagogy; academic achievement